A comparative study of the crystalline structure and mechanical properties of carbon fiber/polyamide 6 composites enhanced with/without silane treatment. Issue 109 (11th November 2016) - Sang, Lin; Wang, YuKai; Chen, Guangyi; Liang, Jicai; Wei, Zhiyong
Abstract : The silane-treated carbon fiber induced the formation of transcrystalline structure and enhanced the interfacial adhesion between the fiber and polyamide 6 matrix. Abstract : Carbon fiber (CF) reinforced polyamide 6 (PA6) composites were manufactured by extrusion compounding and injection molding. The carbon fiber was considered in two forms including untreated and treated with silane coupling agent. The main focus of this study was to investigate the effects of the silane treatment on the mechanical properties and crystalline structure of the composites. Mechanical test results showed that the tensile, impact and flexural strength were significantly increased by incorporation of silane-treated carbon fiber. In particular, the specific tensile, impact and flexural strength of silane-treated CF composites with 20% fibre mass fraction are, respectively, 42%, 51.6% and 30% higher than those of untreated CF composites. Scanning electron microscopy examination showed that the tensile fracture surface of silane-treated CF composites failed in a fiber breakage pattern while the untreated CF composites fractured via a fiber pull-out pattern, suggesting an enhanced interfacial adhesion with the matrix. In addition, the incorporation of silane-treated CF increased the degree of crystallinity, promoted the formation of the thermodynamic crystalline form and induced the specific transcrystalline structure, as indicated by differential scanning calorimetry (DSC), X-ray diffraction (XRD) and polarizing optical microscopy (POM) analysis. Moreover, the mechanism of silane-treated CF reinforced PA6 composites with improved mechanical properties was discussed.